Turning no tides: Union effects on partisan preferences and the working-class metamorphosis - Sinisa Hadziabdic (Max Planck Institute for the Study of Societies, 2023)
Relying on panel data for Germany, Switzerland, the United Kingdom, and the United States, the paper examines the impact of union membership on partisan preferences. By leveraging panel data to control for time-invariant selection effects, we show that unions exert a small consistent left-wing influence on the average wage earner who becomes affiliated, but they are no longer able to modify the preferences of working-class members. A longitudinal approach reveals that changes in partisan preferences can be linked to members' preexisting predispositions and to the prevalent political views within unions. Unions mainly attract individuals who already share their political inclinations before joining. These preexisting left-wing convictions allow an additional left-wing shift to take place through a value congruence mechanism provoked by interactions with long-term union members who are even more left-wing oriented than the newcomers. Symmetrically, working-class joiners exhibit less pronounced left-wing inclinations before becoming affiliated, a gap that widens further after they join as a consequence of their unmet expectations. – – Anhand von Paneldaten für Deutschland, die Schweiz, Großbritannien und die USA wird die Auswirkung der Mitgliedschaft in einer Gewerkschaft auf Parteipräferenzen untersucht. Die Kontrolle zeitinvarianter Selektionseffekte stellt heraus, dass Gewerkschaften einen zwar leichten, aber stetigen linkspolitischen Einfluss auf den durchschnittlichen Arbeitnehmer ausüben, der einer Gewerkschaft beitritt, sie jedoch nicht mehr auf die Präferenzen der Mitglieder der Arbeiterklasse einwirken können. Mit einem longitudinalen Ansatz zeigen wir, dass Veränderungen bei den Parteipräferenzen auf die bereits vorhandenen Neigungen von Mitgliedern und auf die in den Gewerkschaften vorherrschenden politischen Ansichten zurückzuführen sind. Gewerkschaften ziehen vor allem Personen an, die deren politische Gesinnungen bereits teilen. Diese schon bestehenden linken Überzeugungen bewirken einen zusätzlichen Linksruck über einen Mechanismus der Wertekongruenz, der durch Interaktionen mit langjährigen Gewerkschaftsmitgliedern ausgelöst wird, die politisch noch weiter links stehen als jene, die erst vor Kurzem beigetreten sind. Dementsprechend vertreten neue Mitglieder aus der Arbeiterklasse weniger ausgeprägte linke Ansichten, bevor sie einer Gewerkschaft beitreten, und infolge enttäuschter Erwartungen vertiefen sich ihre Überzeugungen, nachdem sie Mitglied geworden sind.
hdl:21.11116/0000-000D-0E50-A
Keywords: 300; Gewerkschaften; Klassen; Paneldaten; politische Parteien; vergleichende Politikwissenschaf; class; comparative politics; panel data; political parties; trade unions